(3QSGdI aj GdYed HGdUajMI GdRQbGdjIs - (3CHh GdhdjO ESeGYjd Hf CMeO GdbQWHis; (3GHf GdRQbGdI , CHh GSMGb,J (B493 (3g` s ((3eMeO GdTgjQ HGdWfWGhi s)
(3ChdgG (B:s
(3bGd GdabjI GdbQWHi QMeg Gddg SCdfi HYV CUMGHi Cf CcJH dge cJGHkG eNJUQkG ai GdYed HhLg UajMI s
(3BNQgG (B:s
(3aEf hbY EdJbG GdeOGQGJ hbS GdWhd GdJi HYO cd hGMO efgG Yf GdeQcR HYO hGMO JMJ MQa GdCab JeJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B79 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B128s
Keywords: (3GdadSaI hGdefWbs